2023
DOI: 10.2147/cia.s395121
|View full text |Cite
|
Sign up to set email alerts
|

A New Scoring System for Predicting Ventricular Arrhythmia Risk in Patients with Acute Myocardial Infarction

Abstract: Objective In this study, a risk score for ventricular arrhythmias (VA) were evaluated for predicting the risk of ventricular arrhythmia (VA) of acute myocardial infarction (AMI) patients. Methods Patients with AMI were divided into two sets according to whether VA occurred during hospitalization. Another cohort was enrolled for external validation. The area under the curve (AUC) of receiver operating characteristic (ROC) was calculated to evaluate the accuracy of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…These damages may end up with HF and even sudden death. In addition, various ventricular arrhythmias may appear in the early stage after heart injury, which can also result in sudden death [ 33 ]. Therefore, patients with AMI are more likely to have serious complications in the early phase after AMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These damages may end up with HF and even sudden death. In addition, various ventricular arrhythmias may appear in the early stage after heart injury, which can also result in sudden death [ 33 ]. Therefore, patients with AMI are more likely to have serious complications in the early phase after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Renal injury in the early stages of AMI has been associated with a poor prognosis in the short term and can increase long-term mortality [ 40 ]. The development of malignant arrhythmias is an important cause of early death in AMI patients [ 33 ]. Early identification of patients at a high risk of various complications is important, and an artificial intelligence model for predicting acute kidney injury risk and a new scoring system for predicting ventricular arrhythmia risk have been developed [ 33 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the short-term, it is established that these patients have a higher risk for cardiovascular mortality and increased risk for MACE (Major Cardiovascular Events) during their hospitalization and shortly after discharge [ 19 ]. These patients' risk for MACE and mortality would be aggravated by concurrent electrolyte disturbances [ 12 ] (e.g., hypokalemia that bares increased risk for arrythmia during myocardial ischemia [ 21 , 22 ]) and pending arrythmias (e.g., prolongation of QTc (QT-corrected) [ 23 ], predisposing to potentially catastrophic ventricular arrythmias. These insights should impose actions on behalf of HAH services organizations: troponin levels should be monitored and accordingly, with respect to the service capacity and capabilities, should be referred to the in-hospital setting or monitored for electrolyte disturbances and/or cardiac conduction anomalies during their hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…
The article titled "A New Scoring System for Predicting Ventricular Arrhythmia (VA) Risk in Patients with Acute Myocardial Infarction (AMI)" by Sun et al has piqued our interest. 1 The objective of the study was to develop a risk score for predicting the occurrence of VA during hospitalization in patients with AMI. The study identified several independent predictors of VA, including a Killip grade of ≥3, STEMI patients, LVEF of <50%, frequent premature ventricular beats, a serum potassium level of <3.5 mmol/L, the presence of type 2 diabetes, and elevated creatinine levels.
…”
mentioning
confidence: 99%